A disposable chitosan-modified carbon fiber electrode for dengue virus envelope protein detection - Cavalcanti, I. T.; Silva, B. V. M.; Peres, N. G.; Moura, P.; Sotomayor, Maria Del Pilar Taboada [UNESP]; Guedes, M. I. F.; Dutra, R. F. (Elsevier B.V., 2012)
A chitosan-modified carbon fiber electrode (CFE) for dengue virus envelope protein (DENV) was developed. Antibodies against DENV were covalently immobilized on the chitosan (CHIT) matrix after activation with sodium periodate. Cyclic voltammetries and scanning electron microscopies analysis were performed to monitor steps involved in the CFE surface modification. Amperometric response of the competitive immunoassays was generated by hydrogen peroxide reaction with the peroxidase conjugated to DENV and 2'-azino-bis-(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) as mediator. The immunosensor showed a lower limit of detection for DENV (0.94 ng mL(-1)) than previously described and a linear range from 1.0 to 175 ng mL(-1), in concentration levels clinically relevant for dengue virus diagnosis. The intra- and inter-assay were respectively 5.8% and 3.6%. The unique and simple design of this immunoassay format provides an economical alternative for the manufacture of other sensitive sensors. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Dengue; Carbon fiber; Immunosensor; Chitosan